2001
DOI: 10.1038/414863a
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 synthesis reduced by red wine

Abstract: Statistical evidence of reduced coronary heart disease in areas of high wine consumption has led to the widespread belief that wine affords a protective effect. Although moderate drinking of any alcohol helps to reduce the incidence of coronary heart disease, there is no clear evidence that red wine confers an additional benefit. Here we show that red wines strongly inhibit the synthesis of endothelin-1, a vasoactive peptide that is crucial in the development of coronary atherosclerosis. Our findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
1
9

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(145 citation statements)
references
References 11 publications
4
131
1
9
Order By: Relevance
“…Corder et al (19) found that RW polyphenols decreased ET-1 synthesis in cultured bovine aortic endothelial cells by suppressing transcription of the ET-1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corder et al (19) found that RW polyphenols decreased ET-1 synthesis in cultured bovine aortic endothelial cells by suppressing transcription of the ET-1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RW phenols blocked endothelin-1 production (19) and induced endothelial nitric oxide synthase (eNOS) expression in cultured endothelial cells (20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, flavonoid-containing beverages increase endothelial production of prostacyclin and suppress production of endothelin-1, a potent endothelium-derived vasoconstrictor (58,59). In regard to regulation of fibrinolysis, catechins and resveratrol increase protein levels and activity of tissue plasminogen activator, an effect that is likely to be cardioprotective (60).…”
Section: Epidemiologymentioning
confidence: 99%
“…Dietary intake of grapevine-based products results in diverse biological effects that are beneficial to human health, in part due to polyphenols, such as flavonoids (e.g., flavonols, proanthocyanidins, and anthocyanins) (Renaud and de Lorgeril, 1992;Corder et al, 2001Corder et al, , 2006Baur et al, 2006). Flavonols, such as kaempferol, quercetin, and isorhamnetin, are an important class of bioactive flavonoids, which are most abundant as their 3-O-glycosides (i.e., glucoside, glucuronoside, galactoside, and rutinoside) in the berries, seeds, and leaves of grapevine (Hmamouchi et al, 1996;Castillo-Munoz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%